THE EFFECTIVENESS OF VIDEO-BASED LEARNING MEDIA TO INCREASE LEARNING MOTIVATION ON ELEMENTARY SCHOOL STUDENTS - Hita, I Putu Agus Dharma; Lestari, Nyoman Ayu Putri; Astuti, Ni Made Ignityas Prima; Fatmawan, Aditya Ridho; Dewi, Made Sri Astika; Kurniawati, Kadek Lina; Isyarotullatifah, Isyarotullatifah; Ilmawan, Anggo Widcaksana (Jurnal Kajian Pembelajaran dan Keilmuan, 2024)
Learning motivation is one of the crucial factors in achieving success in the learning process. This research aims to examine the effectiveness of video-based learning media in improving the learning motivation of elementary school students. A comparative method with the aim of comparing the existence of one variable in two sample groups was used in this study. The research sample consisted of 30 elementary school students in Jembrana Regency, Bali. The experimental group received learning using video-based learning media, while the control group received conventional learning without video media. The analysis results showed a significant difference in the level of learning motivation between the two groups. This finding indicates that the use of video-based learning media can be an effective alternative in improving the learning motivation of elementary school students. The implications of this research highlight the importance of integrating technology in elementary education to create a more engaging and effective learning environment.